El edificio - Buitrago, Jairo (Babel, 2014)
Mr. Levin, a watchmaker, arrives in Bogotá in 1938 and settles into a small apartment building.There he meets Ms. Blanca, and together they watch their city and their neighbors change over the decades. In the 1980s a new tenant arrives -- a small boy who will cause some changes to life in the building